2007
DOI: 10.1007/s00338-007-0284-0
|View full text |Cite
|
Sign up to set email alerts
|

Decadal trends in a coral community and evidence of changed disturbance regime

Abstract: A 23 year data set (1981-2003 inclusive) and the spatially explicit individual-based model ''Compete Ó '' were used to investigate the implications of changing disturbance frequency on cover and taxonomic composition of a shallow coral community at Lizard Island, Australia. Near-vertical in situ stereo-photography was used to estimate rates of coral growth, mortality, recruitment and outcomes of pair-wise competitive interactions for 17 physiognomic groups of hard and soft corals. These data were used to para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 33 publications
3
87
1
Order By: Relevance
“…However, relatively low growth rates have also been reported in the GBR (e.g. < 3 cm yr −1 by Wakeford et al 2008), emphasising the high variability in coral growth rates within and among reefs.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, relatively low growth rates have also been reported in the GBR (e.g. < 3 cm yr −1 by Wakeford et al 2008), emphasising the high variability in coral growth rates within and among reefs.…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, a lower recovery capacity of Acropora has also been observed in some reefs, mainly attributable to environmental conditions or time between disturbances (van Woesik 2000, Berumen & Pratchett 2006). Direct observation as well as modelling have shown monopolization of A. hyacinthus over long intervals without disturbance and limited recovery with ongoing disturbance (Berumen & Pratchett 2006, Wakeford et al 2008). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ecological studies on foraminiferal succession in the Pacific Region are lacking, ecological studies of symbiont-bearing foraminifera in the Florida reef tract have shown that populations recover from bleachingrelated mortality events or hurricane scouring in a matter of months to at most a year or two (Williams et al 1997;Hallock et al 2006, Baker et al 2009). This is in contrast with coral communities which may need decades to fully recover colony density and diversity (Done et al 2007;Wakeford et al 2008). Indeed, paleontological data suggest that foraminiferal assemblages are much more persistent over time than coral assemblages (Tager et al in press).…”
Section: Coralsmentioning
confidence: 99%
“…Coral reefs have evolved under various intensities, modes and frequencies of disturbances, and reef coral populations have experienced severe reduction (Wakeford et al 2008) to complete eradication throughout their evolutionary history (e.g. Veron 1995).…”
Section: Introductionmentioning
confidence: 99%